ANALISIS DISKRIMINASI RASIAL MASYARAKAT ASLI PAPUA DALAM PERSPEKTIF HAK ASASI MANUSIA DAN MULTIKULTURALISME - Mega Arinda Pramessella; Tias Rahma Dewi; Najwa Adhwa Ramadhani; Aniqotul Ummah (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
This research discusses racial discrimination experienced by indigenous Papuans from the perspective of human rights and multiculturalism. This discrimination occurs due to primordialism, ethnocentrism, stereotypers, and discriminatory attitudes that some people have towards the Papuans people. These misperceptions create a negative stigma that Papuans are unequal or less worthy than other groups. Discrimination is also exacerbated by treatment based on factors of race, ethnicity, culture, religion, skin color or physical characteristics that are considered different, as well as policies that do not favor indigenous Papuans. This research uses a transformative paradigm and a qualitative approach with descriptive analysis, based on literature study by analyzing relevant literature. The results show that this discrimination has an impact on structural inequality, cultural, alienation, low access to rights for Papuans, and distrust of state institutions. In addition, ongoing racial discrimination also creates psychological distress and exacerbates the education and economic inequality of the Papuan community. To overcome this racial discrimination, multiculturalism and human rights based policies are essential to create justice and equality for indigenous Papuans.